2016
DOI: 10.1016/j.buildenv.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Quasi steady state and dynamic hygrothermal performance of fibrous Hemp and Stone Wool insulations: Two innovative laboratory based investigations

Abstract: Moisture and heat management properties of Hemp and Stone Wool insulations were studied by mounting them between a hot and a cold climate chamber. Both insulations were exposed to identical hygrothermal boundary conditions. Quasi steady state and dynamic tests were carried out at a range of relative humidity exposures. The likelihood of interstitial condensation was assessed and equivalent thermal conductivity values of the insulations were determined. The adsorption-desorption isotherms of the insulations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Bio-fibre composites can be developed using agro-waste which is widely available. Internal wall bio-based panels optimisation has been studied by other researchers (Arnaud, 2009;Pavlik et al, 2011;Latif et al, 2016;Latif et al, 2018). However, the knowledge on the passive mechanisms and the hygroscopic characteristics associated to these materials is not fully mastered.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-fibre composites can be developed using agro-waste which is widely available. Internal wall bio-based panels optimisation has been studied by other researchers (Arnaud, 2009;Pavlik et al, 2011;Latif et al, 2016;Latif et al, 2018). However, the knowledge on the passive mechanisms and the hygroscopic characteristics associated to these materials is not fully mastered.…”
Section: Introductionmentioning
confidence: 99%
“…and Ferroukhi et al. [[5], [6], [7], [8]]. The experimental device consists of a climatic chamber in order to simulate the outdoor climate conditions and another cell to simulate the indoor conditions, as shown in Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Fig. 6 summarizes the two scenarios that were programmed to apply dynamic boundary conditions to the outer side of the wall, based on previous works [6,[9], [10], [11]]. Temperature and RH data collected at the different depths of the wall, as well as indoor and outdoor conditions are presented in Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Bio-based building materials, especially insulations and envelope-integrated insulation materials, are produced from renewable sourced and show excellent hygric and good to moderate thermal performance [20][21][22]. Takano et al [23], in their study on the energy performance of a hypothetical building model in Finland, observed that the life cycle energy balance of the cellulose fibre insulation was the lowest among all building materials including EPS (expanded polystyrene) and glass wool insulations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%